OPTIMALISASI POTENSI KARYA MAHASISWA MATA KULIAH GRAFIKA DKV MELALUI GALERI ONLINE - Annas Marzuki Sulaiman; Sugiyanto Sugiyanto (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2019)
Graphic reproduction courses or printing methods are one of the courses that always exist in every college of Visual Communication Design in Indonesia, with this course students are expected to understand how the Final Artwork (FA) printing process is correct, the result is the quality of the design work Finally, students have met print-ready standards in accordance with the graphic industry standard so that it has the potential to be offered to the public at large as ready-to-use works, but unfortunately the student's work has only ended up in storage. This study aims to optimize the potential that exists in the final design work to be more widely useful. This study uses a qualitative method with a descriptive approach aimed at analyzing the quality of student design assignments in the Gafika Reproduction Method course, and creating an online gallery as a means of channeling existing design potential